Exploring the therapeutic potential of functional foods for diabetes: A bibliometric analysis and scientific mapping - Wiyono, Nanang; Yudhani, Ratih D.; Wasita, Brian; Suyatmi, Suyatmi; Wardhani, Lusi O.; Pesik, Riza N.; Yarsa, Kristanto Y.; Rahayu, Rachmi F. (Narra Sains Indonesia, 2024)
The incidence of diabetes is increasingly becoming a global health burden. Meanwhile, in recent years, functional foods have been intensively investigated for diabetes management. These foods provide health benefits due to their bioactive compounds that enhance the metabolism and lower the risk of chronic diseases, such as diabetes. The aim of this study was to explore the keywords, countries/territories, publication numbers, institutions, authors, and journals associated with functional foods for the management of diabetes using a comprehensive bibliometric analysis method. Scopus database was used to compile the information, followed by VOSviewer for comprehensive bibliometric data analysis. A total of 1,226 Scopus articles that met the inclusion criteria were analyzed. The results showed that the greatest expansion in research occurred in 2012, and China was identified as the most productive nation in this field. In addition, Food and Function was found as the most recognized journal in this area, and Singh, R.B. as well as Zengin, G. made the greatest contribution. The bibliometric data also illustrated several mechanisms of functional foods for diabetes management, including antioxidant activity, effect on the gastrointestinal microbiomes, and inhibitor α-amylase. These results underscore the immense potential of functional foods in the diabetes management and provide guidance for future research on this subject.